Les indicateurs sont morts, vive les indicateurs! Towards a political economy of S&T indicators: A critical overview of the past 35 years. Issue 1 (14th November 2018) - Barré, Rémi
Abstract: Science and Technology (S&T) indicators are contingent knowledge demanding critique and contextualization for validity: they are value-laden devices. Hence their potential for generating biased knowledge, exhibiting the attributes of devices enabling the social construction of bias and ignorance. But indicators are also prone to criticism and debate, thus, potentially, powerful devices for robust knowledge production. The 80s mark the rise of the new field of S&T indicators aiming at better debates and policies, at the inclusion of science in democracy. Since the mid-90s, there is an extraordinary expansion of S&T indicators field. But the situation today is one of collective blindness through the acceleration of unquestioned S&T activities. To make sense of this situation we contend that (1) S&T indicators have largely become ignorance producing devices, that (2) dominant forces have driven the present design and use of indicators, and that (3) the S&T indicators scientific community, conscious of the drift, has distanced itself since the mid-90s while keeping scientifically active. If the three propositions are correct, then the collective responsibility of the S&T indicators scientific community is to call for an ending of the culturally produced ignorance drift and to pave the way for new designs and uses based on its founding 'science in democracy' problematique.